The contribution of a catchment-scale advice network to successful agricultural drought adaptation in Northern Thailand. (12th December 2022) - Goodwin, Daniel; Holman, Ian; Sutcliffe, Chloe; Salmoral, Gloria; Pardthaisong, Liwa; Visessri, Supattra; Ekkawatpanit, Chaiwat; Rey, Dolores
Abstract : The intensification of drought affects agricultural production, leading to economic losses, environmental degradation and social impacts. To move toward more resilient system configurations requires understanding the processes that shape farmers' adaptation amidst complex institutional contexts. Social networks are an important part of collective action for supporting adaptive capacity and there are continuing calls to strengthen network connectivity for agricultural governance under the impacts of climate change. Through a survey of 176 farmers in northern Thailand, we explore the extent to which the characteristics of information shared in a catchment advice network are associated with adaptations. Statistical analyses reveal the perceived efficacy of communications as well as farmers' relative closeness in the advice network to be positively associated with adaptation to drought. We identify a capacity for local actors to bridge information bottlenecks in the network and opportunities for institutions to enhance their dissemination of information to reach less networked farmers. We find that not all adaptations are perceived as effective against future drought and infer opportunities to support engagement with extension services, encourage the sharing of local knowledge and experience and devise policy and interventions to strengthen advice networks for more resilient agricultural systems. This article is part of the Royal Society Science+ meeting issue 'Drought risk in the Anthropocene'.